Bio-boosting transplants: a systematic review on biopolymers in vascular composite allotransplantation - Knoedler, Leonard; Niederegger, Tobias; Schaschinger, Thomas; Fenske, Jakob; Murugan, Varun P. A.; Knoedler, Samuel; Heiland, Max; Panayi, Adriana C.; Hundeshagen, Gabriel; Lellouch, Alexandre G. (Frontiers in Immunology, 2026)
BackgroundVascularized composite allotransplantation (VCA) joins skin, muscle, bone, nerve, and vessels into a single graft that is both highly immunogenic and mechanically complex. Biopolymers, natural or synthetic, can provide structural scaffolding, localized drug release, and immune modulation. Although widely explored in solid-organ transplantation, their utility in VCA is poorly defined. We therefore conducted a systematic review to consolidate current evidence and map translational priorities.MethodsAdhering to PRISMA 2020 and registered in PROSPERO (CRD420251039845), we searched PubMed, Web of Science, EMBASE, Cochrane Library, and Google Scholar through April 2025. Original studies evaluating biopolymers in any VCA-relevant setting (in vitro, animal, or clinical) were eligible. Clinical quality was judged with the Newcastle-Ottawa Scale and pre-clinical studies with the SYRCLE tool. Given methodological heterogeneity, findings were narratively synthesized.ResultsEleven studies published between 2014 and 2024 fulfilled inclusion criteria. Collectively, they demonstrate that biopolymers, ranging from decellularized limb and auricular scaffolds to collagen-hydroxyapatite or polycaprolactone bone substitutes, hyaluronic-acid–functionalized vascular grafts, chitosan- or alginate-based drug-eluting coatings, and extracellular-matrix (ECM) sheets delivering cytotoxic T-lymphocyte-associated protein 4-immunoglobulin (CTLA4-Ig) with or without rapamycin, consistently enhance vascularization, support multi-tissue regeneration, and preserve mechanical integrity across diverse VCA models. Immunologically, polymer platforms bias host responses toward tolerance: in a murine hind-limb model, ECM combined with CTLA4-Ig and rapamycin extended graft survival to 72 days while promoting pro-regenerative macrophage polarization. Drug-delivery applications also proved effective; calcium-alginate coatings prolonged vancomycin release for up to 50 days in vitro, highlighting the potential for infection control during graft integration. Notwithstanding these benefits, chitosan scaffolds displayed inadequate load-bearing capacity, and heterogeneity in species, graft types, follow-up intervals, and outcome metrics limited direct comparison and impeded meta-analysis.ConclusionBiopolymers emerge as potential adaptable platforms that merge mechanical support with finely tuned immune regulation in VCA. Successful translation will depend on tissue-specific material optimization, standardized immunological endpoints, and multicenter studies that replicate clinical complexity. Drawing on lessons from solid-organ transplantation and fostering collaboration among immunologists, biomaterial scientists, and surgeons will be pivotal to moving these technologies from bench to bedside in VCA.